Entoptic Phenomena in Audio : Categories of Psychedelic Electroacoustic Composition. - Weinel, Jonathan (Contemporary Music Review, 2016)
Altered states of consciousness (ASCs) are perceptual states, such as dream, delirium, or hallucination that fall beyond a commonly accepted normal waking consciousness. This article discussesEntoptic Phenomena in Audio, a collection of four electroacoustic compositions that are based upon the author’s research regarding these states. The compositional process utilised involves consideration of the typical features and structure of hallucinatory experiences, as described by participants in psychological studies and other available literature. Typical features of hallucination are then used to indicate the design of corresponding sonic materials, and the structure of the composition. This compositional process is described in detail, leading to a generalised structural approach for creating electroacoustic compositions based on ASCs, with several possible variations. In addition, the decision to present the works on 12″ vinyl is also discussed, as are the ways in which this project interfaces with electronic dance music culture.